South America's Transnational Solidarity with Southern Africa: Chilean and Argentine Exiles as Cooperators in Mozambique, 1976–1986. - Ayala, Mario; Haristoy, Ricardo Pérez (Journal of Global South Studies)
After declaring the country's independence from Portugal in June 1975, the Mozambique Liberation Front focused its efforts on building a modern nation-state and implementing a development strategy to pave the way for a socialist society. The initial lack of cadres for building and managing a postcolonial national state and the new state economy led it to request the international cooperation and solidarity of the Global Left. The aim of this paper is to analyze the notions and practices of international solidarity among leftist Chilean and Argentine exiles who assumed the role of professional-technical cooperators in independent Mozambique between 1976 and 1986. The working method is based on a qualitative analysis of the information obtained from oral sources, documents of the period, and specialist literature.